The Methodological Opportunities For Developing Professional Self-Development Skills Of Future Educators Based On Dual Education Technology (Journal of Pedagogical Inventions and Practices, 2025)
The rapid development of education and the integration of innovative teaching methods have significantly impacted the professional training of future educators. One of the most promising approaches is dual education, which integrates theoretical knowledge with practical experience in a real-world context. This research focuses on exploring the methodological opportunities for enhancing the professional self-development skills of future educators through dual education technology. The dual education model offers a practical and theoretical framework that allows students to acquire essential skills while working in educational environments. The study examines the importance of fostering professional self-development skills, such as critical thinking, problem-solving, and reflective practice, which are key to the personal and professional growth of educators. Furthermore, it discusses the role of educational institutions in implementing dual education and the benefits this approach brings to the teaching profession. The findings highlight the effectiveness of dual education in shaping skilled and adaptable educators who are equipped to meet the evolving demands of the educational landscape